STRUCTURAL AND FUNCTIONAL DISORDERS OF THE LEFT VENTRICLE IN PATIENTS WITH GOUT - Shodikulova Gulandom Zikriyayevna; Mahmusayev Elyor Jurayevich (Journals Park Publishing, 2022)
Gout is a systemic tofus disease, including recurrent arthritis of peripheral joints due to oversaturation of body fluids with uric acid (UA) in individuals with hyperuricemia (HU) and deposition of sodium monaurate crystals (MUC) in various tissues. The disease is caused by external environmental and/or genetic factors. Asymptomatic HU is a condition with an increased concentration of UA (> 6.8 mg/dl (404 mmol/L)) without joint syndrome and can last for years and be detected accidentally during examination. The cause of  HU in 10% is the excessive formation of UA, in 90% — its impaired excretion. The relationship between increased serum UA levels and cardiovascular diseases (CVD) has been discussed for decades. For the first time, the hypothesis of the association of the MC level with CVD was published in the British Medical Journal in 1886, but only now has the idea of true causal interaction been confirmed thanks to data obtained in the course of numerous clinical and epidemiological studies. In the near future, due to the prevalence of GU, obesity and metabolic disorders, as well as as a result of the aging of mankind, an even greater increase in the frequency of HU and an increase in CVD is expected. This phenomenon is associated with rapid economic development and a change in the lifestyle of a society with a higher socio-economic status. The appointment of urate-reducing therapy should be discussed with each patient. This therapy is indicated for all persons, starting from the first exacerbation of the disease, especially in the presence of tofuses and urate nephropathy. It is recommended to start urate-lowering therapy immediately after diagnosis in patients under 40 years of age and/or in patients with high serum UA levels (more than 8 mg/ dl (480 mmol/L)) and/ or with concomitant diseases such as renal failure, hypertension, coronary artery disease, heart failure, etc.
Keywords: Gout; Arterial hypertension; Left ventricular remodeling